Library Staff Perceptions of Virtual Library and Information Services at Makerere and Uganda Christian Universities, Uganda - Namugera, Lydia; Bukirwa, Joyce; Okello-Obura, Constant (Library Philosophy and Practice, 2025)
This study, which was underpinned by the ServQual model aims to determine the perceptions of library staff of Makerere and Uganda Christian Universities on the provision of virtual library and information services (VLIS), the challenges faced and strategies for the enhancement of VLIS provision. A qualitative design was used to collect data from eight library staff who were selected through purposive sampling until data reached saturation. The findings indicated that majority of librarians exhibit poor perceptions towards VLIS; as manifested in their reluctance to participate in VLIS provision, their conservatism, which impedes acceptance of new VLIS and their failure to apply knowledge and skills obtained during trainings. Several librarians perceive VLIS negatively, viewing VLIS activities as extra work and leaving it to only a few colleagues. In line with the tangibility element of the ServQual model which stipulates appropriate equipment resonates with adoption of new technologies, the study recommends that librarians fully accept, adapt, and provide VLIS in order to remain indispensable in today’s technologically savvy academic environment. Despite the glaring wake-up call for libraries to fully embrace VLIS, it remained limited and the status of its provision not clearly known. This study presents librarians’ perceptions towards VLIS for its enhanced provision. Although some studies exist in the area of virtual library resources, not many have thoroughly examined VLIS, their perceptions, provision and challenges in both public and private universities. This study hence adds to the existing body of literature on how VLIS can be enhanced, especially in developing countries.